Apps-olutely Perfect! Apps to Support Common Core in the History/Social Studies Classroom. Issue 3 (3rd May 2016) - Waters, Stewart; Kenna, Joshua; Bruce, Darrian
ABSTRACT: The inclusion of technology in the classroom is an increasingly important feature of effective instruction. The implementation of Common Core Standards in many states also requires teachers to consider new pedagogical strategies to support meaningful learning. This article explores the intersection between technology demands and curricular change by examining apps that can be used to support Common Core State Standards instruction in history/social studies. Specifically, the authors highlight several apps that they presented at a professional development workshop for six to twelve history/social studies teachers and discuss the teachers' feedback regarding the strengths and limitations of apps to support their instruction. Conclusions are drawn and recommendations for history/social studies teachers using apps in the classroom are provided.